Notti Magiche? Can football narratives shape the idea of a uniform Italian nation and identity? A thematic investigation. - Bernardi, Virginia (Trinity College (Dublin, Ireland). School of Languages, Literature and Cultural Studies, 2021)
This thesis argues that football and sport can constitute a national identity, and Italian identity in particular. With an overview of scholarship on Italian football history, nation building, sports sociology and Italian identity, grounded especially on works by sociologist Benedict Anderson, concerning the imagined status of a nation (2006) and historian John Foot (2007, 2016), football is seen to have a constructive social and political role, and Italy, a disjointed national identity. Research on national imagination through sport is pursued through prominent and relevant themes of language, culture, narrative, belonging, emotion, memory and mediatic influence, identified from existing literature. Thematic analysis is further used to unpack and compare the results of a questionnaire sent out to individuals identifying as Italian, having treated the responses with utmost confidentiality and integrity. â€œNetnographicâ€ and semiotic approaches to social media and media, covering Italy's victory in the 2021 European Championships, supplement and complete the investigation and understanding of the themes observed throughout. The use of different methods and scrutiny of varied content create a work which tackles the vast world of sports sociology and nation building scholarship with diversity, breadth and depth - using the 2021 UEFA European football Championship as a case study. The analysis of celebrations and narratives surrounding Italy's recent victory shows how footballing success grants the Italian nation some of the conditions foregrounded in this paper â€“ unity, belonging, emotion, culture and identification; and how media boost these. This leads to the conclusion that a symbiotic link between football and Italian identity exists, since football is demonstrated to consolidate and restore Italian society, thus to help construct the idea of the Italian nation.
Keywords: Identities and Cultures of Europe